Predictions For The Educational System's Development In The Future (Journal of Namibian Studies : History Politics Culture, 2023)
The current administration has made public the National Education Policy 2020, which sets the way for significant changes to be made to the educational system that is in place throughout the country. This policy is based on the 2030 Agenda for Sustainable Development's five guiding principles, which are access, equality, quality, affordability, and accountability. Each of these principles was designed with the other four principles in mind. As part of the Union Budget 2020-21, the government of India has allotted Rs. 59,845 crore, which is equivalent to approximately $8.56 billion in United States dollars, to the Department of School Education and Literacy and initiated the Revitalizing Infrastructure and Systems in Education (RISE) program. Despite the many attempts to modernize and expand the education system of the nation via comprehensive programs and plans, a significant section of the Indian population does not have access to elementary education. Even though a great number of attempts have been made in this direction, this continues to be the case. This is because many rural communities still do not have sufficient educational facilities or instructors who are competent, despite the advances in technology.